First record of the family Sphyrapodidae Guţu, 1980 (Crustacea: Peracarida: Apseudomorpha) with the description of a new species of Sphyrapus from the Colombian Caribbean - Morales-Núñez,Andrés G.; Morales-Ruiz,Catalina; Ardila,Néstor E. (PeerJ, 2017)
A new sphyrapodid tanaidacean, Sphyrapus caribensis sp. nov. is described and a new record of Kudinopasternakia siegi is reported for the Colombian Caribbean based on samples collected during cruises in 2014–2015. The new species appears to be most closely related to the northeast Atlantic species, Sphyrapus malleolus. Sphyrapus caribensis can be distinguished from Sphyrapus malleolus by a combination of characters, including the maxillipedal basis without long distal seta, the number of setae on the distoventral margin of pereopods 1 and 2, and the number of plumose seta on the pleopod basis. A key for the separation of Sphyrapus species is presented.
Keywords: Tanaidacea; Colombia; Kudinopasternakia; Sphyrapus caribensis; Caribbean; Sphyrapodidae; Deep-sea